Pedagogical contributions to environmental education: a theoretical perspective - Pulido Capurro, Víctor (2018)
The impact of environmental education in the world has had a positive impact on student awareness. However, this problem involves a necessary approach of university pedagogical positions to achieve the effect that is needed in the students and thus achieve the training objective. The purpose of this article is to make known the pedagogical contributions related to three thematic axes: currents in environmental education, didactic approaches and methodological strategies. The methodology used is based on the exhaustive and systematic review of seminal articles and government reports to progressively guide the search towards articles in high impact journals; which has allowed us to reflectively analyze their development over four decades. Therefore, it is intended that the research constitutes a basis for the approach of future pedagogical approaches that allow a better teaching of environmental education in the study contexts, at the basic or higher level. Finally, the research work made it possible to identify the different strategies related to the models worked in national and international educational environments that have made possible the effectiveness of teaching environmental education and its impact on sustainable development.